Dog behavior-sensitive design canine behavior assessment, integrating environmental enrichment in a dog behavioral rehabilitation center in Davao City - Patenio, Jofer Dame G.; Malaque, Isidoro R. III (2020)
Dogs have become quite common in a household. They are loved and considered as part of the family, and in return, the dogs provide security for the family. Just like humans, dogs possess behavioral problems as well. It is confIsidoro R. Malaque IIIed that the environment plays a huge factor in affecting the behavior, as well as its genetics and social experiences. Nowadays, behavioral problems like aggression, fear, and separation anxiety have become quite an issue for dog owners, some owners seek treatment for these types of behavior problems to provide a comfortable life for the dogs. This study mainly conducts an assessment for dogs within Davao City to determine if the said dogs have behavioral problems and determining the Environmental Enrichment needed for dogs. The researcher used the C- BARQ (Canine Behavioral Assessment and Research Questionnaire) to assess the behavior of dogs through owners. The researcher then used a dog owner questionnaire to assess the environment, genetics, and experiences of the dogs. A total of 209 dogs was subjected in the study. Using the data acquired from the questionnaires, the researcher identified the dogs with severe behavioral problems. This population of problematic dogs was separated from dogs free from behavioral problems to determine the differences in its environment, genetics, and social experiences. This part shows that dogs with bad environment influences behavioral problems, as well as its genetics, specifically the size shows that smaller sized dogs are more aggressive that medium to large sized dogs. The results also showed that dogs with bad and traumatic experiences are more prone to bad behavior than those dogs who are spoiled by their owners. With the data collected, the researcher concluded that a good physical environment, genetics, and positive experiences could really shape a dog?s behavior. It is important to check the well-being of dogs from time to time. Constant visits to the veterinarians or trainers could really help ease the behaviors of these dogs.
Thesis (BS Architecture)--University of the Philippines Mindanao,2020